PENINGKATAN MANAJEMEN PENGELOLAAN AIR BERSIH DI PEDESAAN: STUDI KASUS DESA MEKAR SARI - Sugiatmono, Bambang Ribut (BESIRU : Jurnal Pengabdian Masyarakat, 2024)
Clean water management in rural areas is a crucial aspect of improving community welfare. The case study of Mekar Sari Village highlights the importance of effective management in identifying water resources, planning infrastructure development, and ensuring fair and efficient distribution. Management must be able to identify and prioritize community needs based on accurate data. Efficient resource management is important for the success of the program, with optimal allocation of labor, time, and funds. Relevant and well-targeted programs ensure that community needs are met. Continuous evaluation allows management to assess program effectiveness and improve areas where necessary, so that clean water management is always relevant and has a positive impact.